(untitled) (Fiep Bulletin - online, 2011)
INTRODUCTION: A few years ago obesity was considered a disease prevalent among adults, but it has become too common among children and adolescents, and is now considered a worldwide epidemic, affecting the general population, not respecting older or social class. The major factor that causes this effect is the change in lifestyle that the general population has adopted, characterized by a high calorie diet, high stress and physical inactivity. The realization of projects related to obesity, to encourage physical activity and adopt healthy eating habits, it is essential in view of this social problem. OBJECTIVE: This project aimed to clarify the importance of frequent practice of physical activity and a balanced diet, and through hard data and recognized methods, to emphasize to the population served the risks of overweight for health in general and heart. METHODS: We performed physical assessments for Ecological Fair 5R’s (Recycle, reuse, reduce, reforestation and relate), promoted by the network of Adventist education, held at Shopping Cidade das Flores in the city of Joinville, SC, where 144 people were evaluated (92 women and 52 men). The men and women studied had an average body mass index (BMI) acceptable for maintaining overall health but through the Waist-Hip Ratio (WHR) was established a moderate risk for cardiovascular disease in both groups. CONCLUSION: These results demonstrate a propensity for heart disease, urging us to take action cases related to health care, related to changes in lifestyle, by adopting a healthy diet and regular practice of physical activities.